Chainsaw Sound Detection Using DNN Algorithm - Florin Bogdan MARIN; Mihaela MARIN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2023)
Deforestation and illegal logging stand as important environmental problems. In this paper we propose a DNN architecture for sound recognition of chainsaw detection. Various parameters need to be tuned in order to identify the sound of chainsaw but not to produce too much amounts of false positive detection. The task is challenging as different sound emerge in the forest.